HUBUNGAN ANTARA KECERDASAN EMOSI DENGAN PERILAKU ALTRUISTIK PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM JURUSAN DIII PERBANKAN SYARIAH ANGKATAN 2013 UIN RADEN FATAH PALEMBANG - Alfin Yunico; Lukmawati Lukmawati; Midya Botty (Psikis : Jurnal Psikologi Islami, 2016)
This study entitled "The relationship between emotional intelligence and altruistic behavior in the Faculty of Economics and Business of diploma study programme of Islamic Banking in 2013 state islmaic university of Raden Fatah Palembang". This study aims to determine the relationship between emotional intelligence and altruistic behavior in the Faculty of Economics and Business of diploma  study  programme  of  Islamic  Banking  in  2013    state  islmaic  university  of  Raden  Fatah Palembang.  Total  population  in  this  research  were  260  students  registered  as  an  active  student. The  sampling  technique  in  this  research  is  that  using  a  Probability  Sampling  is  Simple  Random Sampling because, the population  sampled everything is homogeneous  students of the Faculty of Economics and Business Islam that serve the student population is 157 students.  This type of research is quantitative correlation. The formulation of the problem is whether there is a relationship between emotional intelligence and altruistic behavior and the contribution or influence of emotional intelligence on altruistic behavior at the Faculty of Economics and  and Business  of    diploma  study  programme  of  Islamic  Banking  in  2013    state  islmaic  university  of Raden  Fatah Palembang.  Methods  of  data  analysis  used  to  test  the  hypothesis  of  the  research  is simple regression analysis   The  results  of  the  analysis  obtained  correlation  coefficient  of  r  =  0.612  with  0.000 significance of p <0.01, so that the results showed that there was a significant positive relationship between emotional intelligence and altruistic behavior in the Faculty of Economics and Business of  diploma  study  programme  of  Islamic  Banking  in  2013    state  islmaic  university  of  Raden  Fatah Palembang.  The  contribution  of emotional  intelligence  to the  altruistic  behavior of  37.4%.  While 62.6% are influenced by other factors.